2016
DOI: 10.1515/aiht-2016-67-2754
|View full text |Cite
|
Sign up to set email alerts
|

How polymorphisms of the cytochrome P450 genes affect ibuprofen and diclofenac metabolism and toxicity / Kako polimorfizmi gena citokroma P450 utječu na metabolizam i toksičnost ibuprofena i diklofenaka

Abstract: Interindividual variability in drug metabolism is an important cause of adverse drug reactions and variability in drug efficiency. Polymorphisms of cytochrome P450 (CYPs) genes have a significant effect on drug metabolism and toxicity. This review brings an update about how genetic polymorphisms of CYP2C8 and CYP2C9 enzymes affect the disposition and clinical outcomes of ibuprofen and diclofenac, two of the most common pain relievers. The most common side effects associated with the influence of CYP2C8*3 and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…The results of metabolizing CYP450 tests demonstrated that at least four major CYP450 isoforms were responsible for the metabolism of LB, which was noticeable considering that DB might be co-administered with other drugs also eliminated by CYP450. For example, promethazine, the standard agent for space motion sickness ( Paule et al, 2004 ), is metabolized by CYP2D ( Litzenburger et al, 2015 ); zolpidem, one of the medications for sleep promotion ( Shi et al, 2003 ), is metabolized by CYP3A ( Hesse et al, 2003 ) and ibuprofen, used for pain relief during spaceflight ( Graebe et al, 2004 ), is metabolized by CYP2C ( Krasniqi et al, 2016 ). Hence, the co-administration of DB with other drugs might lead to potential drug–drug interaction and adverse effects, which should be fully predicted.…”
Section: Resultsmentioning
confidence: 99%
“…The results of metabolizing CYP450 tests demonstrated that at least four major CYP450 isoforms were responsible for the metabolism of LB, which was noticeable considering that DB might be co-administered with other drugs also eliminated by CYP450. For example, promethazine, the standard agent for space motion sickness ( Paule et al, 2004 ), is metabolized by CYP2D ( Litzenburger et al, 2015 ); zolpidem, one of the medications for sleep promotion ( Shi et al, 2003 ), is metabolized by CYP3A ( Hesse et al, 2003 ) and ibuprofen, used for pain relief during spaceflight ( Graebe et al, 2004 ), is metabolized by CYP2C ( Krasniqi et al, 2016 ). Hence, the co-administration of DB with other drugs might lead to potential drug–drug interaction and adverse effects, which should be fully predicted.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme metabolizes many drugs, such as warfarin 33 , phenytoin 34 and non-steroidal anti-inflammatory drugs diclofenac and ibuprofen 35 . Our results show an intermediate prevalence of CYP2C9*2 genotype in KHI (6.8%) as compared to Caucasian (10.4%) and African (0%) populations in HapMap database.…”
Section: Discussionmentioning
confidence: 99%
“…The vast majority of articles are related to pharmacokinetics, metabolism and adverse reactions of NSAIDs, such as gastrointestinal bleeding,26,10,12,13,28 but not the clinical control of inflammatory signs after surgical procedures. Some articles have shown pharmacogenetic impacts on large surgeries, such as the need for prior genetic analysis of patients before bariatric surgeries, regarding the lower use of opioids and lower rates of postoperative pain;29 The study of Murto et al30 shows the impact of CYP2C9*3 on lower postoperative pain rates after adenotonsillectomy surgeries in children taking celecoxib.…”
Section: Discussionmentioning
confidence: 99%